The mystic experience : a descriptive and comparative analysis - Paper, Jordan D. (SUNY series in religious studies., 2004)
"The mystic, zero, or void experience - the ecstatic disappearance of self along with everything else - is considered by those who have had it to be the most beautiful, blissful, positive, profound, and significant experience of their lives. Offering both a descriptive and a comparative perspective, this book explores the mystic experience across cultures as both a human and cultural event. The book begins and ends with descriptions of the author's own mystical experiences, and looks at self-reported experiences by individuals who do not link their experiences to a religious tradition, to determine characteristics of this universal human experience."--Jacket